Effect of maternal anemia on fetal outcome - Akhter, S; Momen, MA; Rahman, MM; Parveen, T; Karim, RK (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):391-8 The abstract of this article is available on the PubMed website